2011
DOI: 10.1007/s10493-011-9465-1
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory response of predatory mites to vegetative and reproductive parts of coconut palm infested by Aceria guerreronis

Abstract: The phytophagous mite Aceria guerreronis Keifer is an important pest of coconut worldwide. A promising method of control for this pest is the use of predatory mites. Neoseiulus baraki (Athias-Henriot) and Proctolaelaps bickleyi Bram are predatory mites found in association with A. guerreronis in the field. To understand how these predators respond to olfactory cues from A. guerreronis and its host plant, the foraging behavior of the predatory mites was investigated in a Y-tube olfactometer and on T-shaped aren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Despite the common occurrence of several predatory mites in association with the coconut mite, field and laboratory observations suggest that many potential predators have difficulties to invade the refuge used by the coconut mite (Lawson-Balagbo et al 2007a;Aratchige et al 2007;Negloh et al 2010;Galvão et al 2011;Lima et al 2012). Among the predators, species of Neoseiulus (Acari: Phytoseiidae) are the most widely tested species in the laboratory (Fernando et al 2003;Aratchige et al 2007;Lawson-Balagbo et al 2007b;Domingos et al 2010;Melo et al 2011;Lima et al 2012) and in field studies (LawsonBalagbo et al 2007a;Fernando et al 2010;Negloh et al 2010). Species of Neoseiulus found on coconuts are dorso-ventrally flattened and have short legs (Chant and McMurtry 2003), which enables them to move in small spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the common occurrence of several predatory mites in association with the coconut mite, field and laboratory observations suggest that many potential predators have difficulties to invade the refuge used by the coconut mite (Lawson-Balagbo et al 2007a;Aratchige et al 2007;Negloh et al 2010;Galvão et al 2011;Lima et al 2012). Among the predators, species of Neoseiulus (Acari: Phytoseiidae) are the most widely tested species in the laboratory (Fernando et al 2003;Aratchige et al 2007;Lawson-Balagbo et al 2007b;Domingos et al 2010;Melo et al 2011;Lima et al 2012) and in field studies (LawsonBalagbo et al 2007a;Fernando et al 2010;Negloh et al 2010). Species of Neoseiulus found on coconuts are dorso-ventrally flattened and have short legs (Chant and McMurtry 2003), which enables them to move in small spaces.…”
Section: Introductionmentioning
confidence: 99%
“…These predatory mites have been extensively studied and represent a potential biological control strategy for A. guerreronis (Kumar and Singh 2000;Moraes and Zacarias 2002;LawsonBalagbo et al 2007aLawsonBalagbo et al , b, 2008Fernando et al 2010;Domingos et al 2010). Among the predators, Neoseiulus baraki (Athias-Henriot) is one of the most widely tested species in the laboratory (Aratchige et al 2007;Domingos et al 2010;Melo et al 2011;Lima et al 2012) and in field studies (Fernando et al 2010), which showed great potential for use in biological control. However, these predators may be affected acaricides used against A. guerreronis (Ramaraju et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to lower costs for producers, reducing the number of applications of acaricides is highly desirable, as this practice is difficult to implement with large crop sizes (Melo et al 2011). The objective of the present study was to identify acaricides that can preserve and increase the native fauna of natural enemies of A. guerreronis.…”
Section: Introductionmentioning
confidence: 99%
“…baraki was described by Melo et al. (), who showed that N . baraki detected chemical cues emitted by coconut plants infested by A .…”
Section: Introductionmentioning
confidence: 74%